2020
DOI: 10.1016/j.scitotenv.2020.137361
|View full text |Cite
|
Sign up to set email alerts
|

Small hydropower plants as a threat to the endangered pearl mussel Margaritifera margaritifera

Abstract: Freshwater mussels are undergoing rapid global declines due to habitat loss and fragmentation, among other factors, but little is known about the effects of small hydropower plants. Here we assessed the impact of small hydropower plants on the abundance and size structure of the imperilled pearl mussel Margaritifera margaritifera. For this, we sampled 66 sites in three Portuguese rivers (Mente, Rabaçal and Tuela) located upstream and downstream of dams and within the reservoirs. Pearl mussels were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
4
31
0
Order By: Relevance
“…In addition, these four sites had wider channels and are subject to higher HFI owing to the proximity of roads, more dense human populations, and more intense agricultural activities. Although not quantitatively evaluated in the present study, earlier assessments showed that all rivers have very similar sedimentological conditions (coarse sediments typical of mountainous rivers), land use and river flow (Sousa et al, 2012; Sousa et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, these four sites had wider channels and are subject to higher HFI owing to the proximity of roads, more dense human populations, and more intense agricultural activities. Although not quantitatively evaluated in the present study, earlier assessments showed that all rivers have very similar sedimentological conditions (coarse sediments typical of mountainous rivers), land use and river flow (Sousa et al, 2012; Sousa et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, given the opportunity (or need) to expand the MNP, we propose an extension to the downstream areas as they display high species richness (some of them with high conservation importance). Besides the possible enlargement of the PA, some management measures should be applied to mitigate the effects of some of the threats in the MNP and surrounding areas, including: control of invasive species such as the signal crayfish Pacifastacus leniusculus and the American mink Neovison vison (Meira et al, 2019; Sousa et al, 2019); improvement of river connectivity by the removal of obsolete physical barriers; better management of the dams to restore more natural river flows and allow fish passage (Schilt, 2007; Sousa et al, 2020); stricter regulation and closer inspection of fisheries (e.g. catch and release or adjustment of minimal length); and an increase in awareness and education programmes in local schools and hunting and fishing associations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the 1960s, several lentic species ( Anodonta suborbiculata , Lasmigona complanata , P. grandis , Utterbackia imbecillis ), that had never been recorded before impoundment, became established as viable populations (Haag, 2012). In Portugal, the construction of small dams in mountainous and oligotrophic rivers was responsible for the near disappearance of the pearl mussel M. margaritifera from areas within the reservoirs, whilst sites located downstream only retained adults without signs of recent recruitment (Sousa, Ferreira, et al, 2020). In Northern Italy, the exponential increase of small hydroelectric plants in the last decade and changes in agricultural practices (e.g.…”
Section: Anthropogenic Habitats As Stable Refuges or Ecological Trapsmentioning
confidence: 99%
“…Consequently, the proliferation of small reservoirs throughout south‐eastern Australian rivers, especially in the Murray–Darling Basin (Kingsford, 2000), may create mixed conservation outcomes. The most significant environmental alterations, which explained the observed patterns in reservoirs, were related to changes in sediment characteristics (accumulation of fine sediments and organic matter), temperature, suspended solids and dissolved oxygen (Haag, 2012; Sousa, Ferreira, et al, 2020).…”
Section: Anthropogenic Habitats As Stable Refuges or Ecological Trapsmentioning
confidence: 99%